Access, education and literacy: key themes in Information Science between the years 2013 and 2022 (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The project "Information Science: what we have done, where we are, and where we are going?" investigated the main themes in Information Science in Brazil between 2013 and 2022. Applied and quantitative in nature, it analyzed 1,683 publications from four A1 journals: "Dados," "Informação e Sociedade: estudos," "Perspectivas em Ciência da Informação," and "Transinformação." Utilizing Knowledge Discovery in Texts (KDT) and Text Mining in the stages of Collection, Preprocessing, Indexing, Mining, and Analysis, with R language, the results indicated that "Access," "Education," and "Information Literacy" were central themes, with the latter emerging in recent years.
Keywords: knowledge discovery in texts; information retrieval; text minin; research line; concentration area